The 1980 Aparejo Glacier catastrophic detachment: new insights and current status - Ugalde, Felipe; Casassa, Gino; Marangunic, Cedomir; Fernandoy, Francisco; Carrasco, Jorge; Buglio, Franco (Frontiers in Water, 2024)
The catastrophic detachment of Aparejo Glacier (one of the three known cases in the Andes) took place on 1 March 1980 and resulted in the removal of an ice volume initially estimated to be 7.2 Mm 3 , which originally was 1.0 km long and covered an area of 0.2 km 2 . The event caused the sudden mobilization of the sliding mass 3.7 km down valley at an estimated speed of 110 km/h, causing remarkable geomorphological changes, including the obliteration of most of the glacier. 40 years after the event, we analyze new evidence: 3 ground surveys carried out in 2015 and 2016; DEMs and glacier outlines compiled from orthorectified aerial imagery pre-and post-event; GNSS data; Ground Penetrating Radar (GPR) data; a terrestrial LiDAR scan survey of 2020, together with detailed interviews with 2 direct witnesses of the event, terrestrial and helicopter-borne photographs acquired 12 days after the sudden detachment. The combined interpretation of these new data, allow us to make a more precise estimation of the pre-detachment glacier volume, 12.9  0.6 × 10 6 m 3 and the detached ice volume of 11.7  0.6 × 10 6 m 3 (90% of the total volume of the glacier). We also show that in the 40-year period Aparejo Glacier has recovered 12,4% of the original glacier volume, with a mean ice thickness of 19.5 m and a maximum of 40 m according to GPR data, being preserved within the same basin as the detached glacier. In recent years, the glacier has shown a mean elevation change of -3.7 ± 1.2 m during the 2015-2020 period, with maximum thinning values greater than 8 m, which are probably caused by enhanced ablation due to climate warming and reduced precipitation during the current megadrought which started in 2010 and has lasted more than 1 decade. We conclude that under the projected scenarios of climate warming and reduced precipitation for central Chile, the risk associated to a new detachment of Aparejo Glacier is unlikely.